ZAKAT PRODUKTIF DAN PENINGKATAN KESEJAHTERAAN MUSTAHIK: STUDI PEMBERDAYAAN EKONOMI BERBASIS SYARIAH - Nur Aeni (Lembaga Pengembangan Kinerja Dosen, 2025)
Productive zakat is an Islamic economic instrument with significant potential to improve the welfare of mustahik through Sharia-based economic empowerment. This study aims to analyze the effectiveness of productive zakat in enhancing the living standards of mustahik and to identify the key factors contributing to its success. This research employs a qualitative approach using a case study method on several productive zakat programs implemented by zakat management institutions in Indonesia. The findings indicate that productive zakat not only increases mustahik’s income but also promotes economic independence and strengthens their social resilience. The key success factors of these programs include continuous mentoring, transparent governance, and synergy among various stakeholders. The implications of this study highlight the importance of optimizing the management of productive zakat to contribute more significantly to poverty alleviation and the creation of a more inclusive economy.